Enterprise Security Maturity Model for the Banking and Financial Industry from EA (Enterprise Architecture) Perspective - Bawachkar, Hrushikesh (Digital Repository of Theses, 2025)
When analysed from the perspective of enterprise architecture (EA), the enterprise security maturity model (ESMM) for the banking and financial sector provides a crucial foundation for improving security procedures in an industry that is constantly threatened by changing cyber threats. Having strong security is now essential for organizational viability and regulatory compliance, not just a priority as digital technologies continue to transform the financial sector. By dividing security measures into several maturity levels that are in line with business goals and IT infrastructure, the ESMM acts as a guide for financial institutions as they methodically evaluate, enhance, and change their security policies. The function of enterprise architecture is fundamental to this change. EA acts as the blueprint to guarantee that security is viewed as an essential component of the organization's larger goals, procedures, and systems rather than as a stand-alone function. Banks and other financial organizations can match security measures to IT infrastructure, Digital Assets, business objectives, data Policies and regulatory constraints by integrating security into EA. This synchronization is essential, especially for the banking industry, where adherence to legislation like the Payment Card Industry Data Security Standard (PCI DSS), the General Data Protection Regulation (GDPR), and other local banking laws is required. Serious fines, harm to one's reputation, and monetary loss may arise from breaking these rules. Additionally, the Purpose of this research is that ESMM to provide financial institutions with a methodical approach to developing a security posture that changes in tandem with the ever-changing threat landscape. Organizations can take a proactive stance by regularly evaluating and enhancing their security capabilities, thanks to the ESMM. Financial organizations can create a more robust security architecture that can withstand both present and emerging threats by moving through the maturity levels. Intent this research is to build a thorough ESSM framework for enhancing security in the financial and banking sectors by integrating the ESMM with Enterprise Architecture and achieve a) Improved risk management function , b) Strategic alignments leading to better co-operation and co-ordination across departments, c) Compliance and regulatory benefits d) Informed security budgets, and e) long-term sustainability